Multiple bacteria contribute to intraplaque T-cell activation in atherosclerosis - Van Der Meer, J. J.; Van Der Wal, A. C.; Teeling, P.; Idu, M. M.; Van Der Ende, A.; De Boer, O. J. (European journal of clinical investigation, 2008)
Background  Infection with microorganisms is considered a pathogenic factor in atherogenesis. Several studies have shown the presence of a broad spectrum of bacterial species in atherosclerotic plaques, which could trigger local inflammation. Because T cells contribute to atherosclerotic plaque inflammation, we studied the responsiveness of human plaque derived T‐cell cultures to bacteria of different species. Materials and methods  Primary polyclonal T‐cell cultures were generated from both carotid endarterectomy tissue and peripheral blood of nine patients, and the peripheral blood of eight matched controls. The in vitro proliferative responses of the T‐cell cultures against H. pylori, N. meningitidis, N. lactamica, S. aureus, S. pneumoniae, S. epidermidis and E. coli were analysed. T‐cell proliferation was measured by 3H‐thymidine incorporation and expressed as a stimulation index. Selective outgrowth of intraplaque microbial specific T cells was studied by calculating the ratio of plaque T‐cell SI and peripheral blood T‐cell SI in each patient. Results  All patients showed T‐cell responsiveness to multiple bacteria in their plaque tissue. Stimulation indices were in the range of 0·3–30, and this degree of reactivity with the different species was heterogeneous among patients. Selective outgrowth (plaque/peripheral blood ratio) of T cells against multiple bacteria was observed in six out of nine patients. Conclusions  T cells in atherosclerotic plaques have the capacity to selectively respond to antigens of a wide variety of microbial antigens. This supports the view that such mechanisms could contribute to the atherosclerotic inflammatory response.